1986
DOI: 10.1128/mcb.6.12.4149
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 2 peptide IX gene is expressed only on replicated DNA molecules.

Abstract: Transcription of the adenovirus type 2 peptide IX (pIX) gene was examined in transient expression assays. When a nonreplicating plasmid DNA containing the pIX gene was introduced into HeLa cells by the DEAE-dextran method, no pIX gene transcript was detected. In contrast, efficient transcription was observed in the cells transfected with a replicating plasmid containing the pIX gene. Adenovirus early genes did not affect the level of transcription of the pIX gene on either a nonreplicating or a replicating pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
2
19
1
Order By: Relevance
“…We do not know to what extent transiently introduced DNA is organized in nucleoprotein structures reflective of stable chromatin, nor can we determine what fraction of this DNA actually serves as a template. Results from these systems may selectively emphasize the role of protein-protein contacts, although replication of the DNA template has been shown to be important for some responses even in transient expression analysis (6,24). In this regard, we have recently demonstrated that hyperacetylation of histones causes the MMTV promoter to become refractory to hormone stimulation and nucleosome displacement (7).…”
Section: Discussionmentioning
confidence: 99%
“…We do not know to what extent transiently introduced DNA is organized in nucleoprotein structures reflective of stable chromatin, nor can we determine what fraction of this DNA actually serves as a template. Results from these systems may selectively emphasize the role of protein-protein contacts, although replication of the DNA template has been shown to be important for some responses even in transient expression analysis (6,24). In this regard, we have recently demonstrated that hyperacetylation of histones causes the MMTV promoter to become refractory to hormone stimulation and nucleosome displacement (7).…”
Section: Discussionmentioning
confidence: 99%
“…The pIX gene encodes a capsid protein and is expressed late (Crossland & Raskas, 1983). A number of investigators have attempted to elucidate the mechanisms controlling these transcriptional switches, with inconsistent results (Crossland & Raskas, 1983;Matsui et al, 1986;Venkatesh & Chinnadurai, 1987;Vales & DarneU, 1989). For instance, earlier work suggested that viral DNA replication was a prerequisite for activation of the pIX gene.…”
Section: Introductionmentioning
confidence: 99%
“…I and others have previously reported that transcription of the adenovirus 2 peptide IX (pIX) gene is activated by DNA replication in a transient expression assay (19,27). Transcription of the pIX gene occurred only on DNA molecules that had been replicated in transfected HeLa cells.…”
mentioning
confidence: 99%